The effect of dephasing on superadiabatic single-qubit rotation gates - Ahmed, Gharib Subhi Mahmoud; Az Eddine, Messikh (IOP Publishing Ltd., 2017)
To implement quantum gates stimulated Raman adiabatic passage (STIRAP) can be used. This STIRAP requires high Rabi frequencies and to overcome this problem we use superadiabatic approach. Our model is a tripod consisting of four-level system driven by three resonant fields. These fields are modulated by Gaussian pulses with different amplitudes, phases and time delays. We investigate the robustness of our model against dephasing which are caused by collisions or phase fluctuations of the fields.